2015
DOI: 10.1016/j.jhealeco.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sign-dependent societal preferences for quality of life

Abstract: ABSTRACT. This paper is the first to apply prospect theory to societal health-related decision making. In particular, we allow for utility curvature, equity weighting, sign-dependence, and loss aversion in choices concerning quality of life of other people. We find substantial inequity aversion, both for gains and losses, which can be attributed to both diminishing marginal utility and differential weighting of better-off and worse-off. There are also clear framing effects, which violate expected utility. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…There have been a number of previous empirical studies of health inequality aversion using the same basic questionnaire instrument in England (Williams et al ., ; Dolan and Tsuchiya, ; Dolan and Tsuchiya, ; Dolan and Tsuchiya, ) and Spain (Abásolo and Tsuchiya, ; Abásolo and Tsuchiya, ; Abásolo and Tsuchiya, ). All of these studies have found that the majority of the population is willing to sacrifice a substantial amount of total health in order to reduce health inequality, as have most studies using different instruments (Edlin et al ., ; Attema et al ., ). In most cases, it is not possible to extract comparable inequality aversion parameter central estimates, because parameters were not reported or are not comparable.…”
Section: Discussionmentioning
confidence: 97%
“…There have been a number of previous empirical studies of health inequality aversion using the same basic questionnaire instrument in England (Williams et al ., ; Dolan and Tsuchiya, ; Dolan and Tsuchiya, ; Dolan and Tsuchiya, ) and Spain (Abásolo and Tsuchiya, ; Abásolo and Tsuchiya, ; Abásolo and Tsuchiya, ). All of these studies have found that the majority of the population is willing to sacrifice a substantial amount of total health in order to reduce health inequality, as have most studies using different instruments (Edlin et al ., ; Attema et al ., ). In most cases, it is not possible to extract comparable inequality aversion parameter central estimates, because parameters were not reported or are not comparable.…”
Section: Discussionmentioning
confidence: 97%
“…This seems to be caused by a general tendency to be pessimistic about one's own health compared to peers' health in the VAS tasks. When splitting the dataset into three age groups (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), 56-75), we found VAS_OWN to be lower than VAS_OTHER for each separate age class as well (paired t-tests: all p < 0.01), making this finding universal across age. Because the residuals were heteroscedastic (White's test, p < 0.01), we conducted a regression with White heteroscedasticity-consistent standard errors to test Hypothesis 2.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper we combine the data of three separate online surveys, administered by the authors of this paper in 2013 and 2014. Two of these are reported elsewhere [28,29]. The three surveys aimed to elicit individual and societal preferences for health outcomes 1 and all contained a number of questions about relative health (see Table 5), which were not used for the aforementioned papers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If one takes the position of “empirical ethics,” however, then social welfare judgments should also be based on preferences of the individuals. In that case, it becomes relevant that many individuals do not reason within the expected utility framework that is underlying our analysis (see, e.g., Attema, Brouwer, l'Haridon, & Pinto, ). Although we believe that empirical research on value judgments is very useful (see Gaertner and Schokkaert, ), we do not think that average subjective preferences should dictate the social objective that is used in CBA and we believe that there are good normative reasons to adopt the SWF with a sensitivity analysis for ρ .…”
Section: Theoretical Backgroundmentioning
confidence: 99%